Controllable Synthesis of Nanosized Amorphous MoSx Using Temporally Shaped Femtosecond Laser for Highly Efficient Electrochemical Hydrogen Production. (14th November 2018) - Li, Bo; Jiang, Lan; Li, Xin; Cheng, Zhihua; Ran, Peng; Zuo, Pei; Qu, Liangti; Zhang, Jiatao; Lu, Yongfeng
Abstract: Amorphous molybdenum sulfide (a‐MoS x ) is regarded as a promising electrocatalyst for hydrogen evolution reaction (HER) due to its disorder structures with a significant number of defect‐rich active sites. Here, a green, one‐step, and controllable method is developed to photoregulate the chemical reactions and synthesize nanosized a‐MoS x by temporally shaped femtosecond laser ablation of ammonium tetrathiomolybdate aqueous solution. By adjusting the laser energy and pulse delay to control photoinduced and/or photothermal‐induced reduction/oxidation, the S to Mo ratio x can be modulated from 1.53 to 3.07 and the ratio of the Mo V defect species, bridging S2 2−, and terminal S2 2− ligands can be controlled. The optimized a‐MoS x catalysts ( x = 2.73) exhibit high catalytic activity with a low Tafel slope of 40 mV dec −1, high double‐layer capacitance of 74.47 mF cm −2, and large current density of 516 mA cm −2 at an overpotential of 250 mV. The high catalytic activity can be mainly attributed to Mo V defect species and bridging S2 2− ligands, or most likely dominated by the Mo V defect species. This study not only provides an alternatively controllable method to prepare a‐MoS x as efficient HER catalysts but also contributes to the understanding of the origin of its catalytic activity. Abstract : For the first time, various material compositions of nanosized amorphous MoS x (from amorphous MoS2 to amorphous MoS3 ) are successfully synthesized through photomodulation of the reaction mechanisms (from photothermal‐induced to photoinduced reduction/oxidation). The catalysts with optimized ratios of active sites of Mo V defect species, bridging S2 2− ligands, and terminal S2 2− ligands exhibit excellent catalytic activity.